MICE dan Non-MICE dalam rangka menetapkan strategi event management - Handayani, Vivi Tri; Rofii, Muhammad Syaroni; Syahputra, Alfin Reza (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Procurement of events or what is commonly referred to as events is something that is very common at this time. Events have various purposes and also have various procurement scales. Some events are known to fail in their implementation and even cause riots. This can happen due to a lack of attention to event management. Event management will be easier to do by classifying events. The classification of events that are well known in the event business world are MICE events and non-MICE events. MICE events include meetings, incentive trips, conferences and exhibitions. Non-MICE events consist of festivals, sports tourism, celebrations and parties. Broadly speaking, event management consists of 5 stages, including: research, design, planning, coordination, and evaluation. However, each event characteristic has a different treatment of these 5 things. The purpose of this study is to examine the concept of events and efforts to avoid event failures due to a lack of understanding of events. The study used a descriptive qualitative method with a literature review approach in which a conceptual study was carried out regarding each event to find an appropriate formulation of the event concept for each class. This research results that the failure of an event can have a serious impact such as the occurrence of riots where one of them occurred in Indonesia, event failures can also raise their own fear of customer disappointment. Both MICE events and non-MICE events must pay attention to their characteristics and important points such as location, room, event concept, event protocol, participants, event scale and so on. It can be concluded that knowing the characteristics of an event can make it easier to develop event concepts and carry out event management both at the pre-event, during the event, and after the event.